2022
DOI: 10.3390/biom12121739
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cellular Uptake and Permeation of Curcumin Using a Novel Polymer-Surfactant Formulation

Abstract: Several therapeutically active molecules are poorly water-soluble, thereby creating a challenge for pharmaceutical scientists to develop an active solution for their oral drug delivery. This study aimed to investigate the potential for novel polymer-surfactant-based formulations (designated A and B) to improve the solubility and permeability of curcumin. A solubility study and characterization studies (FTIR, DSC and XRD) were conducted for the various formulations. The cytotoxicity of formulations and commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…Sixty minute after treating cells with free curcumin and PVP-Cur NPs, it was shown that the relative fluorescence intensity of curcumin loaded into the nanoparticles was 1.5 times higher than that of the free curcumin ( Figure 4 ). This difference in the absorption is due to the presence of an amphiphilic poly(N-vinylpyrrolidone) shell and correlates with other studies related to curcumin encapsulation [ 53 , 54 ].…”
Section: Resultssupporting
confidence: 86%
“…Sixty minute after treating cells with free curcumin and PVP-Cur NPs, it was shown that the relative fluorescence intensity of curcumin loaded into the nanoparticles was 1.5 times higher than that of the free curcumin ( Figure 4 ). This difference in the absorption is due to the presence of an amphiphilic poly(N-vinylpyrrolidone) shell and correlates with other studies related to curcumin encapsulation [ 53 , 54 ].…”
Section: Resultssupporting
confidence: 86%
“…The amorphous state is a high-energy state over the crystalline state, and, thus, the long time period of stable existence needs fine compatibility between the co-existence components to prevent possible solid-phase separation [ 78 , 79 , 80 ]. FTIR spectra can be exploited to disclose the possible secondary interactions between the components, which include hydrogen bonding, electrostatic interactions, hydrophobic interactions, and Van Der Waals forces and are favorable to high stability [ 81 , 82 , 83 ]. The ATR-FTIR spectra of the raw materials (ATP, PVP, and CA) and their electrosprayed products (P1, P2, and P3) are included in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the amazing properties offered by LDHs, their low solubilization in water, agglomeration, and unsatisfactory targeted delivery have limited the potential of LDHs in CRF [5]. To deal with the aforementioned limitations, LDHs were attempted to be incorporated with a wide range of new materials, including polymeric surfactants [6][7][8]. Owing to the ability of polymeric surfactants to manipulate the nature of LDHs, predominantly in terms of size distribution, size of the particle, morphology, surface interaction, and zeta potential, this ability has therefore assisted in making LDHs more favorable for drug encapsulation [2,[7][8].…”
Section: ■ Introductionmentioning
confidence: 99%